KEANEKARAGAMAN ARTROPODA DAN STRUKTUR POPULASI KUMBANG BADAK DAN KUMBANG TANDUK DI LAHAN PERKEBUNAN KELAPA SAWIT - Akmal, Akmal (Fakultas Pertanian Universitas Mataram, 2025)
Changes in the growth phase of oil palm can potentially affect the population dynamics of rhinoceros beetles (Oryctes rhinoceros L.) and horned beetles (Xylotrupes gideon L.), two major pest species that can reduce plantation productivity. This study aims to identify the population structure of the two beetle species and the diversity of arthropods in oil palm plantations in two locations with different growth phases, namely immature plants (TBM) and producing plants (TM). The results showed that the rhino beetle preadult population was only found in the TM location with an average population of 8.71 ± 18.21 individuals/plot, while the horned beetle was found in both locations with a higher population in the TBM location (30.13 ± 18.25 individuals/plot) compared to TM (22.33 ± 12.66 individuals/plot). The population structure of rhinoceros beetles was dominated by instar I and II larvae, while horned beetles were dominated by instar I, II, and III larvae. In addition, the diversity of arthropods in the TM site was higher than that in the TBM site, especially when sampling using the berlese funnel method. These findings have important implications for pest management in oil palm plantations, especially in minimizing losses due to pests with a plant growth phase-based approach and biodiversity management.